Isolation of a circulating CD45-, CD34dim cell population and validation of their endothelial phenotype - Tropea, Margaret M.; Harper, Bonnie J. A.; Graninger, Grace M.; Phillips, Terry M.; Ferreyra, Gabriela; Mostowski, Howard S.; Danner, Robert L.; Suffredini, Anthony F.; Solomon, Michael A. (Thrombosis and Haemostasis, 2014)
Accurately detecting circulating endothelial cells (CECs) is important since their enumeration has been proposed as a biomarker to measure injury to the vascular endothelium. However, there is no single methodology for determining CECs in blood, making comparison across studies difficult. Many methods for detecting CECs rely on characteristic cell surface markers and cell viability indicators, but lack secondary validation. Here, a CEC population in healthy adult human subjects was identified by flow cytometry as CD45-, CD34dim that is comparable to a previously described CD45-, CD31bright population. In addition, nuclear staining with 7-aminoactinomycin D (7-AAD) was employed as a standard technique to exclude dead cells. Unexpectedly, the CD45-, CD34dim, 7-AAD- CECs lacked surface detectable CD146, a commonly used marker of CECs. Furthermore, light microscopy revealed this cell population to be composed primarily of large cells without a clearly defined nucleus. Nevertheless, immunostains still demonstrated the presence of the lectin Ulex europaeus and von Willebrand factor. Ultramicro analytical immunochemistry assays for the endothelial cell proteins CD31, CD34, CD62E, CD105, CD141, CD144 and vWF indicated these cells possess an endothelial phenotype. However, only a small amount of RNA, which was mostly degraded, could be isolated from these cells. Thus the majority of CECs in healthy individuals as defined by CD45-, CD34dim, and 7-AAD- have shed their CD146 surface marker and are senescent cells without an identifiable nucleus and lacking RNA of sufficient quantity and quality for transcriptomal analysis. This study highlights the importance of secondary validation of CEC identification.
Keywords: Vascular cell markers; gene expression; flow cytometry; viability; circulating endothelial cells